IMK Inflation Monitor: Inflation differentials between households considerably lower in May 2023 - Sebastian Dullien; Silke Tober (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2023)
Germany's CPI inflation stood at 6.1% in May 2023 and was thus more than one percentage point lower than in April 2023 (7.2%). Food prices contributed slightly less to inflation, but at 2.1 percentage points still almost seven times as much as usual. The contribution of household energy was nine times higher than in more normal times, albeit with a lower weight in the consumer price index than food. Total energy prices increased by only 2.6% as fuel prices significantly fell over the past 12 months ( 14.2%). Core inflation excluding energy, food, alcohol, and tobacco also declined and stood at 5.0% in May 2023 after 5.5% in April 2023. Prices for household energy increased by 17.4% year on year, followed by food and non-alcoholic beverages (14.5%). As the share of food and household energy in consumption expenditure is strongly correlated with income, there are still noticeable differences between household-specific inflation rates. In May 2023, the range of household-specific inflation rates was 1.5 percentage points. Low-income single adults, who benefited little from falling gasoline prices, had by far the highest inflation rate (6.9%), high-income single adults - as continuously since February 2022 - the lowest (5.4%). The difference in the combined burden of food and household-energy prices remains particularly pronounced. It amounted to 2.8 percentage points, with food and household energy contributing 4.7 percentage points to inflation for low-income single adults, compared to 1.9 percentage points for high-income single adults.
Keywords: 330; Inflation; haushaltsspezifische Inflationsraten; Energiepreise; Nahrungsmittelpreise